The evaluation of compliance with the basise of uncollectibility of the goals of punishment with each others in the penal code of Afghanistan-with an emphasis on administrative corruption crimes - Mohammad Iqbal Haqyar; Syed Baqer Mohammadi (مطالعات تطبیقی حقوق کشورهای اسلامی)
The most obvious types of complexity of sentencing is compliance with the process based on which the legislator can achieve the goals of punishment.The purposeful penalization model is trying to determine the territory of criminal intervention, provide the possibility of the existence of other tools and institutions of social control, and introduce its own foundations and principles.One of the basises of this model is the uncollectibility of the goals of punishment with each others.In practice, it is not possible to fully combine the goals of punishment in one or more types of punishments, which in the model of purposeful penalization, the same non-fulfillment of the goals of punishment is considered as the basis of the uncollectibility of the goals of punishment with each other.In this work, how to comply with the basis of uncollectibility of punishment objectives in the penal code of Afghanistan from the perspective of the mentioned model with emphasis on administrative corruption crimes is evaluated and it shows that the basis of uncollectibility of punishment is in 13 discourses which include 1 discourses of general orders and 12 discourses of crimes and punishments (administrative corruption) have not been observed.This work suggests that in amendment of the mentioned penal code, while observing the findings of this research, the uncollectibility of the goals of punishment should be observed in other parts of the penal code as well.